Peran Kader PPTI Dalam Pemberantasan Penyakit Tuberkulosis di Kabupaten Buleleng - I Nyoman Suprapta (Jurnal Widya Mahavira, 2025)
The Province of Bali is one of the provinces in Indonesia that still faces challenges in controlling Tuberculosis (TB). Specifically in Buleleng Regency, the latest data indicate that there are 583 tuberculosis patients. In this context, the role of PPTI cadres (Indonesian Tuberculosis Eradication Association) in tuberculosis control programs is greatly needed. With a total of 120 cadres, the ratio of cadres to TB patients is 1:6. Based on the results of the study, it was found that the methods used by PPTI cadres of the Buleleng Branch in disseminating information about tuberculosis include: (1) providing education to the community about tuberculosis, its prevention, and treatment; (2) increasing community participation in the eradication of tuberculosis; and (3) conducting education and training for the community to serve as cadres, educators, and drug-taking supervisors. It was also found that, as motivators, PPTI cadres of the Buleleng Branch carry out roles such as providing assistance to tuberculosis patients, conducting routine supervision of tuberculosis patients, and motivating patients to undergo treatment until recovery. PPTI cadres, who do not receive financial compensation, voluntarily carry out their duties and responsibilities as the frontline in tuberculosis control efforts.